Influence of transformational leadership, organizational citizenship behavior, and worker involvement on innovative work performance with sharing of knowledge as an intervening variable at the Office of PLP Class II Tanjung Uban, Ministry of Transportation - Sirait, Amri; Dewi, Nolla Puspita; Rumengan, Angelina E. (Goodwood Publishing, 2023)
Purpose: This study aimed to analyze the influence of transformational leadership, organizational citizenship behavior, and work involvement on innovative work behavior, with knowledge sharing as an intervening variable. Research Methodology: This research used a quantitative approach with a survey method. A total of 101 employees were selected using total sampling method. Data were collected through questionnaires and analyzed using structural equation modeling-partial least squares (SEM-PLS) version 3.0. Results: The findings indicate that transformational leadership, OCB, and work involvement significantly affect innovative work behavior. OCB and work involvement significantly influenced knowledge sharing, whereas transformational leadership did not. Knowledge sharing itself does not significantly affect innovative work behavior and does not mediate the relationship between the independent variables and innovative work behavior. Conclusions: Innovative work behavior is primarily shaped by leadership, citizenship behavior, and employee involvement, whereas knowledge sharing plays only a limited role. Strengthening OCB and engagement directly enhances innovation, even without mediation by knowledge sharing. Limitations: This study was restricted to one institution and relied only on questionnaires. Contribution: This study highlights the importance of leadership, OCB, and involvement in fostering innovation, offering guidance for managerial practice.